Combustion syntheses of Co3O4 powders using different fuels - Gardey Merino, Maria Celeste (2015)
Co3O4 powders are used as pigment in solar selective paints. In this work, two new gel-combustion processes for the synthesis of Co3O4 nanopowders with lysine (Lys) or ethylenediaminetetraacetic acid (Edta) as fuel are presented. The first route is a conventional, stoichiometric process, while the second one is a non-stoichiometric, pH-controlled process. The samples were calcined in air at 500 ºC. They were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared spectrum (FTIR), Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) and the optical properties of the pigments were assessed with a spectrophotometer. In all cases, powders exhibited the Co3O4 crystalline structure. A minimum crystallite average size of 19 nm for powders obtained by the ?stoichiometric/Lys? combustion route was observed, meanwhile, a maximum value of 47 nm was stated for powders obtained by the ?non-stoichiometric/Edta? combustion process. The average particle size ranged between 50 and 100 nm. The powders obtained by the stoichiometric nitrate?lysine route were selected to study its optical properties, their solar absorption was 88%, compared with the references, evidencing their aptitude to be used in solar absorbent paints.